Methods for Assessment of Viability and Germination of Plasmodiophora brassicae Resting Spores - Wang, Yao; Koopmann, Birger; von Tiedemann, Andreas (Frontiers in Microbiology, 2022)
Clubroot caused by the obligate biotrophic parasite Plasmodiophora brassicae is a destructive soil borne disease of cruciferous crops. Resting spores of P. brassicae can survive in the soil for a long period without hosts or external stimulants. The viability and germination rate of resting spores are crucial factors of the inoculum potential in the field. The accurate assessment of viability and germination rate is the foundation to evaluate the effect of control methods. In this study, we evaluated several methods for the assessment of viability and germination rate of P. brassicae resting spores. Dual staining with calcofluor white-propidium iodide (CFW-PI) or single stain with Evans blue showed reliable accuracy in estimating viability. CFW-PI was capable of reliably determining the viability within 10 min, while Evans blue required a much longer exposure time to obtain accurate results. Due to DNA degradation of heat treatments, acetone was selected to evaluate the efficiency of PMA-qPCR used for the quantification of DNA from viable cells. The staining with 4,6-Diamidine-2-phenylindole dihydrochloride (DAPI) and the use of differential interference contrast microscopy were suitable for the determination of resting spore germination rates. The latter method also allowed recording individual germination states of spores. Alternatively, dual staining with CFW-Nile red was successfully used to assess the germination rate of resting spores with a lethal pre-treatment. This study evaluates and confirms the suitability of various microscopic and molecular genetic methods for the determination of viability and germination of P. brassicae resting spores. Such methods are required to study factors in the soil regulating survival, dormancy and germination of P. brassicae resting spores causing clubroot disease in Brassicaceae hosts and therefore are fundamental to develop novel strategies of control.